A prospective study evaluating tobramycin pharmacokinetics and optimal once daily dosing in burn patients. Issue 8 (December 2017) - Lee, Colin; Walker, Sandra A.N.; Walker, Scott E.; Seto, Winnie; Simor, Andrew; Jeschke, Marc
Highlights: <20% total burn surface area (TBSA) injury causes altered tobramycin pharmacokinetics. Once daily dosing of tobramycin can be considered in burn patients with <20% TBSA. Tobramycin dosed at 10 mg/kg may be required when given once daily. Abstract: Background: Once-daily aminoglycoside dosing (ODA) is used in most patient populations to optimize antibacterial activity and reduce toxicity. Unfortunately, burn patients are excluded from ODA due to concerns over altered pharmacokinetics resulting in a shortened half-life and low peak aminoglycoside concentrations. Retrospective studies suggest that ODA may be appropriate if higher milligram/kilogram doses are used. However, no prospective clinical trials in burn patients exist to confirm these findings. Objective: To determine the adequacy of once daily tobramycin dosed at 10 mg/kg in adult burn patients. Methods: This prospective single dose pharmacokinetic clinical trial was conducted at the Ross Tilley Burn Centre. Patients with a total burn surface area (TBSA) of <20% and creatinine clearance ≥50 mL/min were eligible. A first-order one compartment model was used to determine the pharmacokinetic profile from 3 or 5 tobramycin levels over a 24 h period per patient. Monte Carlo simulation (MCS) was performed to determine the probability of target level attainment. Results: The mean percent TBSA, partial, and full thickness burn were 10%, 6%, and 4%, respectively. Nine of the ten patients recruited achieved peak concentrations of ≥20 mg/L (mean of 29.4 ± 5.7 mg/L) and all patients had a trough level ≤0.5 mg/L. The mean half-life, volume of distribution, and clearance were 2.58 h, 0.33 L/kg, and 7.40 L/h, respectively. The MCS determined probability of attaining target peak concentrations with the 10 mg/kg dose was 97%, which almost doubled that predicted with the usual 7 mg/kg dose. Conclusion: Burn patients with adequate renal function and <20% TBSA are candidates for ODA. Tobramycin half-life was similar to healthy, non-burn patients. The larger than normal volume of distribution supports the use of the higher empiric dose of 10 mg/kg total body or adjusted weight in non-obese and obese patients, respectively, with further dose adjustment based on therapeutic drug monitoring.